2009
DOI: 10.1186/1471-2164-10-260
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling within the spleen of Clostridium perfringens- challenged Broilers fed antibiotic-medicated and non-medicated diets

Abstract: Background: Clostridium perfringens (Cp) is a Gram-positive anaerobic bacterium that causes necrotic enteritis (NE) in poultry when it overgrows in the small intestine. NE disease has previously been controlled through the use of growth-promoting antibiotics. This practice was recently banned in European countries, leading to significantly increased incidence of NE threatening the poultry industry. Control strategies and technology as substitutes to dietary antibiotics are therefore urgently required. To devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 60 publications
3
16
0
Order By: Relevance
“…Based on these results, the authors concluded that both cell-mediated and antibody-mediated immune responses were responsible for the host defense against C. perfringens infection. In a subsequent microarray study, Sarson et al (2009) confirmed that the expression of genes involved in inflammation, humoral immunity, antigen recognition, apoptosis, and immune-related metabolic processes were significantly altered after experimental infection of chickens with C. perfringens.…”
Section: Cytokine and Toll-like Receptor Expressionsupporting
confidence: 73%
“…Based on these results, the authors concluded that both cell-mediated and antibody-mediated immune responses were responsible for the host defense against C. perfringens infection. In a subsequent microarray study, Sarson et al (2009) confirmed that the expression of genes involved in inflammation, humoral immunity, antigen recognition, apoptosis, and immune-related metabolic processes were significantly altered after experimental infection of chickens with C. perfringens.…”
Section: Cytokine and Toll-like Receptor Expressionsupporting
confidence: 73%
“…Unlike a short oligonucleotide library, a long oligo nucleotide microarray can provide significantly improved sensitivity and can even detect one single transcript in one cell [18]. Previous studies have shown that the 44K Agilent chicken long oligonucleotide microarray can provide reliable results by detecting different chicken tissues [19]. Moreover, in order to improve the accuracy, three tissues from different individuals were pooled together for RNA extraction and hybridization in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The chickens used for the present study were the same birds used for our previous reports of alpha-toxin gene expression in the chicken intestine (35) and the host response to C. perfringens infection as evaluated by both a low-density chicken immune cDNA microarray and a 44,000-slide-format whole-chicken-genome Agilent microarray (34,42). The chickens were cared for under the 1993 guidelines of the Canadian Council on Animal Care.…”
Section: Bacteriummentioning
confidence: 99%